Field report, summer 1978 - Greer, Janet G.et al (1978)
Field report for the summer of 1978 submitted by Janet G. Greer. A note regarding the absence of sightings of Ruby-throated Hummingbirds during the spring and summer of that year is underlined. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer, 1978. Epson - sheet feed/flatbed